The Role of Osteopenia in Oral Bone Loss and Periodontal Disease - Wactawski-Wende, Jean; Grossi, Sara G; Trevisan, Maurizio; Genco, Robert J; Tezal, Miné; Dunford, Robert G; Ho, Alex W; Hausmann, Ernest; Hreshchyshyn, Myroslaw M (Journal of periodontology (1970), 1996)
Osteoporosis and periodontitis are diseases which affect a large number of women and men, with incidence increasing with advancing age. Osteopenia is a reduction in bone mass due to an imbalance between bone resorption and formation, favoring resorption, resulting in demineralization and leading to osteoporosis. Osteoporosis is a disease characterized by low bone mass and fragility and a consequent increase in fracture risk. Periodontitis is characterized by inflammation of the supporting tissues of the teeth, resulting in resorption of the alveolar bone as well as loss of the soft tissue attachment to the tooth and is a major cause of tooth loss and edentulousness in adults. The relationship of osteopenia to oral bone loss and periodontal disease has been addressed in a limited number of studies. A review of current knowledge regarding this relationship is presented. Interpretation of the literature is complicated by the variety of methods used to assess osteopenia, oral bone mass, and periodontitis, as well as varying definitions of outcomes of interest. Results of a previously unpublished study are presented which suggest that severity of osteopenia is related to loss of alveolar crestal height and tooth loss in post-menopausal women. The literature on the relationship among these disorders is limited and points to the need for additional studies which thoroughly evaluate the influence of potential confounding factors to further define the relationship between low bone mineral density and periodontal disease in larger populations. Clearer understanding of this relationship may aid health care providers in their efforts to detect and prevent osteoporosis and periodontal disease. Increased dialogue among medical and dental professionals will be increasingly important in achieving and maintaining patients' optimal health. J Periodontol 1996;67:1076-1084.